Sintering behaviour and characterisation of low-cost ceramic foams from coal gangue and waste quartz sand. (2nd October 2016) - Li, Z.; Li, X.; Tang, Y.; Liu, T.; Wu, T.; Hao, X.; Lu, A.
Abstract : New ceramic foams have been successfully synthesised with coal gangue and waste quartz sand, which supply a feasible way to recycle these hazardous solid wastes. An objective of this research was to investigate the sintering behaviour and effects of sintering conditions on the crystalline phase change, microstructure and main properties of final ceramic foams. Good correlations among porosity, thermal conductivity, water absorption, bulk density, mechanical properties were studied. Results indicated that increasing sintering temperature or time had similar effects on the physical–mechanical properties. Samples sintering at 1140°C for 1 hour exhibited the highest porosity (87.5%), lowest bulk density (0.39 × 10 −3  kg m −3 ), lowest thermal conductivity (0.085 W·(m K) −1 ), moderate water absorption (9.38%) and adequate flexible strength (2.4 MPa). Combined with excellent properties and low-cost characteristics, the new development for ceramic foams preparation will be widely used in building insulation materials for no-load bearing walls.